Growth-stimulating effect of transferrin on a hybridoma cell line: relation to transferrin iron-transporting function - Kovár, J; Franĕk, F (Experimental cell research, 1989)
The relation of the growth-stimulating capacity of transferrin to its iron-transporting function was investigated in mouse hybridoma PLV-01 cells cultivated in a chemically defined medium. The cells were precultivated in protein-free medium supplemented either with ferric citrate (cells with a high intracellular iron level) or with iron-saturated transferrin (cells with a low intracellular iron level). Iron uptake was monitored after the application of 59Fe-labeled ferric citrate or pig transferrin. Cultivation of the cells at the optimum growth-stimulating concentration (500 microM) of ferric citrate resulted in an intracellular iron level about 100-fold higher than that of cells cultivated at the optimum transferrin concentration (5 micrograms/ml). Replacement of pig transferrin with bovine transferrin resulted in similar intracellular iron levels, but the growth-stimulating effect of bovine transferrin was more than one order of magnitude lower. Cells with a high intracellular iron level grew equally well when cultivated with iron-saturated transferrin or with apotransferrin + deferoxamine (2 micrograms/ml). On the other hand, cells with a low intracellular iron level required iron-saturated transferrin for further growth and apotransferrin + deferoxamine was ineffective. The results suggest that transferrin can act as a cell growth factor only in the iron-saturated form. However, several findings of this work indicate that supplying cells with iron cannot be accepted as the full explanation of the transferrin growth-stimulating effect.
Keywords: Cattle; transferin; buněčné dělení; Animals; skot; Hybridomas; Kinetics; železo; Mice; prasata; Transferrin; Culture Media; kultivované buňky; myši; Cells, Cultured; kultivační média; Iron; Swine; zvířata; Cell Division; kinetika; hybridomy